Analysis of Credit Risk Differences Based on Risk Management and Related Banking Regulation : Case Study of Banks in Indonesia and Malaysia - Tika Larasati Harjito Putri (Politeknik Ganesha Medan, 2025)
Currently, banks in Indonesia face extortionate loan interest rates due to high credit risks in disbursing loan. This is different from what happens in Malaysia, which has lower credit risk and cheaper credit interest rates. This makes it difficult for banks in Indonesia to achieve loan growth target set by Bank Indonesia in the last 3 years and they are considered not optimal in distributing loan. It happened since they focused more on how to gain more loan profit than do loan expansion. This explanatory case study research aims to investigate and explain reasons behind high credit risk based on risk management and related banking regulation implemented in Indonesia and Malaysia and its impact on bank performance such as NIM and loan productivity. Descriptive analysis was used to explain result of data analysis and information obtained from official websites of Bank Mandiri, Bank BRI, and Bank UOB Malaysia for the period 2021 – 2023. This study contributes to provide policy advice for Indonesia banking regulator to control credit risks as part of loan interest rate calculations in order to optimalize bank performance.